2013
DOI: 10.1007/s00339-013-8065-9
|View full text |Cite
|
Sign up to set email alerts
|

Ga-vacancy-induced room-temperature ferromagnetic and adjusted-band-gap behaviors in GaN nanoparticles

Abstract: Room-temperature ferromagnetism has been found in Ga-deficient GaN grown using the direct reaction of Ga 2 O 3 powder with NH 3 gas. The observed magnetism in GaN induced by Ga vacancies is investigated both experimentally and theoretically. First-principles calculations reveal that the spontaneous spin polarization is created by the 3.0 μ B local moment for GaN and magnetism originates from the polarization of the unpaired 2 p electrons of N surrounding the Ga vacancy. At the same time, the band gap can be al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Nonetheless, the origin and mechanism of DIM in GaN-based DMSs also have not reached a unanimous opinion so far. For instance, some experimental researchers observe room temperature ferromagnetism (RTFM) in GaN nanoparticles or films and attribute it to Ga-related vacancies [13][14][15]. However, ferromagnetism cannot reach to room temperature when the vacancy density is lower than 10 21 cm −3 , which has been predicted by theoretical calculations [16].…”
Section: Introductionmentioning
confidence: 96%
“…Nonetheless, the origin and mechanism of DIM in GaN-based DMSs also have not reached a unanimous opinion so far. For instance, some experimental researchers observe room temperature ferromagnetism (RTFM) in GaN nanoparticles or films and attribute it to Ga-related vacancies [13][14][15]. However, ferromagnetism cannot reach to room temperature when the vacancy density is lower than 10 21 cm −3 , which has been predicted by theoretical calculations [16].…”
Section: Introductionmentioning
confidence: 96%
“…% (sample 3) causes V Ga point-defects that could participate in the generation of ferromagnetism, as other authors have suggested. Ren et al and Jeganathan et al 44,45 recently reported ferromagnetism in gallium-deficient GaN nanoparticles and nanowires, respectively, in which both groups vary the Ga flux during the synthesis of the nanostructures and correlate the gallium deficiency, detected by EDS or XPS, to the generation of V Ga . These measures were correlated with PL measurements that confirmed the presence of gallium vacancies due to its electronic transitions, similarly to the CL measurements present in this work, because the sensitivity of these techniques to detect the characteristic defect-related optical transition has been broadly demonstrated.…”
Section: -5mentioning
confidence: 99%
“…More detailed experiments showed that the optical absorption edge moved to longer wavelengths (red-shifted) as the concentration of Ga vacancies increased [ 112 ]. Figure 3 shows the effect of Ga vacancy on UV-vis spectrum of GaN nanoparticles.…”
Section: Physical Properties and Applications Of Gan Nanoparticlesmentioning
confidence: 99%
“…The band-gap of GaN nanoparticles increased with decreasing concentration of Ga vacancy. The band-gap of Ga N nanparticles with the concentration of Ga vacancy of 2.8% was , for Ga N nanoparticles with the concentration of Ga vacancy of 1.8%, and for Ga N nanoparticles with the concentration of Ga vacancy of 1.6% [ 112 ].…”
Section: Physical Properties and Applications Of Gan Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation